Evaluation of Natural Enemy Abundance Based on Riparian Vegetation at Rice Field in Slamet Village, East Java, Indonesia - Faidatu Ummi; Catur Retnaningdyah; Bagyo Yanuwiadi (Universitas Brawijaya, 2023)
Riparian vegetation habitats in irrigation canals provide various ecosystem regulatory services for human life. One of them was providing a habitat of natural enemies for agricultural pests. This research aims to evaluate the community structure of natural enemies based on the diversity index and abundance value, and riparian vegetation community in the four different categories of tertiary irrigation canals at the Slamet Village rice field. Arthropods were observed using a visual encounter survey and yellow pan trap methods for fifteen days. At the same time, riparian vegetation analysis was also applied by purposive sampling. The results showed that the first location of irrigation canals had the highest Shannon-Wiener diversity index, taxa richness, evenness, and the lowest dominance value of riparian vegetation with respectively 4.97; 37 species; 0.93; and 0.02. Moreover, it was followed by high natural enemy’s taxa richness based on yellow pan trap and visual encounter survey (16 and 28 families), total abundance (554 and 4450 individuals), diversity index (1.83 and 3.67), evenness index (0.77 and 0.68), and low dominance index (0.22 and 0.21). Arthropods that act as natural enemies commonly found in this location came from the Formicidae, Coenagrionidae, and Coccinelidae families, while the most common pests found were from the Acrididae family. The opposite of that, the fourth location had a high dominance index of riparian vegetation (0.15), diversity index of pest (1.83), taxa richness of pest (10 families), and 272 individuals of pest arthropod arthropods. The highest abundance of pests in this location came from the Acrididae, Drosophilidae, Tephritidae, and Aphididae families.